(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
A pedagogical principle is defined at different levels, from the very abstract down to the micro context of individual tutor beliefs that form the basis for their planned and spontaneous classroom action. Pedagogic is the science concerned with the teaching and learning process of the younger generation. Because, methods also deal with the problems of educating and learning, it is most closely integrated to pedagogics. In studying foreign language teaching one must know pedagogics. One of the branches of pedagogics is called didactics. Didactics investigates general ways of teaching in schools. Methods, as compared to didactics, studies the certain ways of teaching a definite subject.